Investigating the Determinant and Impact of Digital Library Engagement: A Conceptual Framework – - Mohamad Rahimi Mohamad Rosman; Mohd Nasir Ismail; Mohamad Noorman Masrek (Journal of Digital Information Management, 2019)
Facing an unprecedented explosion and growth of Information and Communication Technology (ICT) signal the overwhelming dependency on the digital library (DL). Over the years, libraries spent a great amount of investment to subscribe to various digital resources such as online databases, electronic journals, electronic books and other digital resources. However, previous studies reported that the use of DL is underutilized; hence undermining its original purposes and making it harder for the libraries to justify their investment on DL resources. It is reported that users prefer to use free online resources compared to the DL resources. The lack of DL usage is credited to the lack of DL engagement and the impact of contextual factors leading to DL engagement. Yet, not much is known about the contributing factors of DL engagement as well as its impacts. Therefore, the purpose of this paper is twofold: (1) to introduce the concept of Digital Library Engagement, and (2) to discuss at the conceptual level on the determinants and impacts of digital library engagement and development of a conceptual framework. In order to develop the conceptual framework, the study adopted a systematic literature review approach of over 100 papers. Grounded in previous literature on DL, the contributions of this paper are as follows: first, the paper provides insight on the new concept of digital library engagement; second, the paper proposes